THE INFLUENCE OF PRODUCT INNOVATION, SOCIAL MEDIA AND BRAND IMAGE ON CUSTOMER PRODUCT PURCHASE DECISIONS ERIGO FASHION - Fadillah Fikriansyah; Suadi Sapta Putra; Kumba Digdowiseiso (Jurnal Ekonomi, 2023)
This research aims to find out how much influence Product Innovation, Social Media and Brand Image have on Erigo Fashion Brand buyers' decisions and the most dominant factors in Erigo fashion brand purchasing decisions. Reliability and Validity Tests were carried out with 100 respondents and the results showed that the question items were proven to be valid and reliable for use in further analysis. The population in this research are buyers of the Erigo Fashion Brand. A questionnaire was used to collect data from 100 respondents. The data analysis used in this research is quantitative analysis using SPSS Version 22. The test results show that the coefficient of determination seen in the value of R square = 0.844 = 84.4% means that the independent variables are Product Innovation, Social Media and Brand Image together. the same contributed 84.4% and the remaining 16.6% was influenced by other variables that were not included in this research.